CURRENCY AND ITS ROLE IN MODERN ECONOMIES - Bolbekova Ug'iloy Jaloliddinovna; Urunova Ruxshona Faxriddin qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  article  examines  the  economic  essence,  historical  evolution,  major functions, and contemporary significance of currency in modern economies. The study explains the transformation of currency from barter and commodity-based exchange to metallic money, paper banknotes, fiat currency, and digital monetary forms. Particular attention is given to the role of currency in market exchange, price formation, savings accumulation,  deferred  payments,  and  macroeconomic  stability.  The  article  also analyzes  the  relationship  between  currency,  inflation,  exchange  rates,  and technological  innovation  in  the  financial  sphere.  The  findings  demonstrate  that currency is not merely a technical means of payment, but a fundamental institutional mechanism that supports economic coordination, financial intermediation, and national development. In the context of globalization and digitalization, the future of currency depends on the effective interaction of innovation, public trust, monetary regulation, and financial security.